The automotive chassis engineering principles : chassis and vehicle overall, wheel suspensions and types of drive, axle kinematics and elastokinematics, steering, springing, tyres, construction and calculations advice. - Reimpell, Jornsen; Stoll, Helmut; Betzler, Jurgen W. (Oxford : Butterworth Heinemann, 2001)
This comprehensive overview of chassis technology presents an up-to-date picture for vehicle construction and design engineers in education and industry. The book acts as an introduction to the engineering design of the automobile's fundamental mechanical systems. Clear text and first class diagrams are used to relate basic engineering principles to the particular requirements of the chassis. In addition, the 2nd edition of 'The Automotive Chassis' has a new author team and has been completely updated to include new technology in total vehicle and suspension design, including platform concept and four-wheel drive technology.
Types of suspension and drive -- Tyres and wheels -- Wheel travel and elastokinematics -- Steering -- Springing -- Chassis and vehicle overall.
Previous ed.: / by Jornsen Reimpell and Helmut Stoll. London : Arnold, 1996.
Includes bibliographical references and index.
Keywords: Motor vehicles -- Chassis -- Design and construction; Electronic books